2015
DOI: 10.1161/circulationaha.114.013801
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Use and Adverse Outcomes Associated with Transvenous Lead Removal in the United States

Abstract: Background— Transvenous lead removal (TLR) has made significant progress with respect to innovation, efficacy, and safety. However, limited data exist regarding trends in use and adverse outcomes outside the centers of considerable experience for TLR. The aim of our study was to examine use patterns, frequency of adverse events, and influence of hospital volume on complications. Methods and Results— Using the Nationwide Inpatient Sample, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
52
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(56 citation statements)
references
References 33 publications
3
52
0
1
Order By: Relevance
“…The incremental financial burden associated with reintervention in our study was $68 000 to treat an infection and $36 000 to treat a mechanical failure, and the average costs for the year before and the year after a complication were elevated if a patient had an infection. This is in consonance with other studies that suggest that the healthcare expenditure associated with infections and reinterventions could be astronomical 22, 23, 24…”
Section: Discussionsupporting
confidence: 91%
“…The incremental financial burden associated with reintervention in our study was $68 000 to treat an infection and $36 000 to treat a mechanical failure, and the average costs for the year before and the year after a complication were elevated if a patient had an infection. This is in consonance with other studies that suggest that the healthcare expenditure associated with infections and reinterventions could be astronomical 22, 23, 24…”
Section: Discussionsupporting
confidence: 91%
“…3 Randomized prospective trials in this field are lacking. 3 Randomized prospective trials in this field are lacking.…”
Section: Defining the Problemmentioning
confidence: 99%
“…9 Hybrid procedures designed to avoid sternotomy and the consequent morbidity have been reported. [2][3][4][5][6][7][8][9][10] The SVC-RA junction remains the site most prone to injury. These have included novel methods like retrograde laser use via right atriotomy 8 and direct visualization of the SVC-RA junction by a limited local thoracotomy or thoracoscopy.…”
Section: The Collaborative Electrophysiologist and Cardiac Surgeon Exmentioning
confidence: 99%
“…According to the data from the National Cardiovascular Data Registry of the United States of America, major complications occurred in 2.3% among a total of 11 304 TLE procedures and urgent cardiac surgeries were required in 16% of those . Previous reports have demonstrated that a higher number of extracted leads are associated with a higher risk of complications and a long‐term mortality . In the latest ESC‐EHRA European Lead Extraction registry, more than three lead extractions are an independent predictor of a cardiac avulsion or tear with a tamponade .…”
Section: Discussionmentioning
confidence: 99%